Rapid Formation of Self‐Supporting Polydimethylsiloxane Sheets with Periodic Clusters of Embedded Nickel Nanoparticles. Issue 9 (10th March 2021) - Rega, Romina; Muñoz Martinez, Juan Francisco; Pagliarulo, Vito; Longo, Angela; Palomba, Mariano; Carotenuto, Gianfranco; Ferraro, Pietro; Grilli, Simonetta
Abstract: The direct and rapid formation of a precise pattern of metallic nanoparticles (NPs) supported and/or embedded in a flexible polymeric substrate is not easy to achive. However, the development of simpler and more reliable procedures is still highly desirable. This paper presents an innovative technique, simple, cheap, and robust, for producing a self‐supported sheet of polydimethylsiloxane (PDMS) embedding periodic arrays of clusters of nickel nanoparticles (NiNPs). The method uses the pyroelectric effect in a periodically poled lithium niobate (PPLN) crystal for producing a surface charge template able to address the patterning of the NPs by applying a simple thermal stimulation. The key advantages are rapidity, single‐step, and electrode‐free operation. The reliability of the technique is demonstrated for different geometries that are called here "dots" and "grid" and for three different periods 50, 200, and 400 µm. The resulting sheets are attractive for both their flexibility and magnetic properties that can be used for detection, entrapment, and/or patterning of micro‐ and nanoparticles in various fields such as microfluidics and biomedicine. Abstract : An innovative, extremely simple, cost‐effective, and robust technique for producing a self‐supporting sheet of polydimethylsiloxane incorporating periodic arrays of nickel nanoparticle clusters is presented. This is possible thanks to the pyroelectric effect in a periodically poled lithium niobate crystal. Due to a simple thermal stimulation, a surface charge pattern is generated on the ferroelectric crystal capable of organizing clusters of nanoparticles in periodic geometries.